Transformation of Hospital Occupational Safety and Health as a Pillar of Medical Personnel Resilience and Patient Safety Quality at St. Ann’s Bay Regional Hospital, Ocho Rios - Thelwell-Reid, Marcia (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aims to analyze the effectiveness of K3RS implementation from the aspects of policy, safety facilities, and medical personnel preparedness as the main pillars of improving patient safety and protecting health workers. Methodology: The research method uses a quantitative descriptive approach with survey techniques on medical and health workers, supplemented by data analysis through frequency and percentage distribution. Main Findings: The results of the study indicate that all three aspects of K3RS implementation are in the very good category, indicated by high average scores for regulatory completeness, availability of safety facilities, and a high level of medical personnel preparedness in facing occupational risks. These findings are supported by previous research that confirms that K3RS effectiveness has a direct impact on improving service quality and reducing safety incidents. Novelty/Originality of this study: The novelty of this research lies in the integration of the analysis of medical personnel resilience with patient safety quality in the context of the transformation of the K3RS system after the hospital management reform, which has not been widely explored in previous research